2015
DOI: 10.1002/jcc.24255
|View full text |Cite
|
Sign up to set email alerts
|

Sparsity‐weighted outlier FLOODing (OFLOOD) method: Efficient rare event sampling method using sparsity of distribution

Abstract: As an extension of the Outlier FLOODing (OFLOOD) method [Harada et al., J. Comput. Chem. 2015, 36, 763], the sparsity of the outliers defined by a hierarchical clustering algorithm, FlexDice, was considered to achieve an efficient conformational search as sparsity-weighted "OFLOOD." In OFLOOD, FlexDice detects areas of sparse distribution as outliers. The outliers are regarded as candidates that have high potential to promote conformational transitions and are employed as initial structures for conformational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 48 publications
1
23
0
Order By: Relevance
“…S2 and S4 in Supporting Information). In OFLOOD, initial structures (outliers) always located at edges of conformational distributions in our previous studies …”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…S2 and S4 in Supporting Information). In OFLOOD, initial structures (outliers) always located at edges of conformational distributions in our previous studies …”
Section: Resultsmentioning
confidence: 64%
“…Judging from the assessments for the different numbers of initial structures, one might need to confirm whether the total number of initial structures is sufficient for reproducing structural transitions of a given protein with reasonable computational costs. Although it is desirable to independently perform trials with different numbers of initial structures and assess their conformational sampling efficiencies, as far as we have experienced, N initial should be a set of no more than 100 for the actual applications of relevant protein dynamics including protein folding, large‐amplitude motions, and induced fit processes …”
Section: Resultsmentioning
confidence: 99%
“…As one of the representative enhanced conformational sampling techniques developed by us, outlier flooding method (OFLOOD), has been proposed as a rare event sampling technique by combining a physical science‐based method with an information science‐based method, that is, MD simulation with a hierarchical clustering method. Figure shows the concept of OFLOOD.…”
Section: Introductionmentioning
confidence: 99%
“…Although the detailed dynamics cannot be pursued, free energy landscapes (FEL) can be estimated by the umbrella sampling or a Markov state model (MSM) once the transition pathways among (meta-) stable structures are obtained. [23,24] As one of the representative enhanced conformational sampling techniques developed by us, outlier flooding method (OFLOOD), [30][31][32][33] has been proposed as a rare event sampling technique by combining a physical science-based method with an information science-based method, that is, MD simulation with a hierarchical clustering method. Figure 1 shows the concept of OFLOOD.…”
Section: Introductionmentioning
confidence: 99%
“…Shaw et al have reported that the folding processes of these mini‐proteins might be relatively complicated and different from a simple two‐state folding between unfolded and their native states, indicating that there might exist multiple folding pathways. Actually, our previous studies have also reported a possibility that the mini‐proteins such as Trp‐cage and Villin have multiple folding routes, and there exist intermediate states during the folding pathways. Herein, it seems that the partial formations of secondary structures in the early process might play a major role in the fast‐folding of these mini‐proteins, because proteins have characteristic secondary structures as partial elements in their native structures.…”
Section: Introductionmentioning
confidence: 99%